The Effect of Cooperative Learning on Mathematics Learning Outcomes Viewed from Studentsâ Learning Motivation - Razak, Firda ((JRAMathEdu) Journal of Research and Advances in Mathematics Education, 2016)
This experimental research was aimed to reveal the effect of cooperative learning models viewed from the level of learning motivation on studentsâ learning achievement on mathematics. The data were analyzed using the Two-Way ANOVA. The conclusions of this study are: (1) there were effects of interaction between cooperative learning models (TPS and NHT) and learning motivation on mathematics learning achievement, (2) the mathematics learning achievement of students with high level of learning motivation who were taught using TPS model is higher than those who were taught using NHT, and (3) the mathematics learning achievement of the students with low level learning motivation who were taught using TPS model is insignificantly different than those who were taught using NHT.